1994
DOI: 10.1021/bi00199a029
|View full text |Cite
|
Sign up to set email alerts
|

Specific Nucleus as the Transition State for Protein Folding: Evidence from the Lattice Model

Abstract: We have studied the folding mechanism of lattice model 36-mer proteins. Using a simulated annealing procedure in sequence space, we have designed sequences to have sufficiently low energy in a given target conformation, which plays the role of the native structure in our study. The sequence design algorithm generated sequences for which the native structures is a pronounced global energy minimum. Then, designed sequences were subjected to lattice Monte Carlo simulations of folding. In each run, starting from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
451
2
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 476 publications
(492 citation statements)
references
References 66 publications
36
451
2
3
Order By: Relevance
“…The original MJ potential (Table V of [329]), as was used in [40,153,296,330], embodies the hydrophobic effect, thus it tends to place non-polar residues in the folded protein core as in real proteins (reviewed in [116,204]). However, certain modified, 'shifted' forms of MJ potentials that are similar to table VI of [329] with prominent repulsive energies [331] do not embody this biophysical property (reviewed in [158,204]), making it problematic to interpret some of the predictions from such models. For instance, in some cases, a shifted-MJ potential may lead to nominally charged residues instead of hydrophobic residues occupying the core of a model protein [114,204,331].…”
Section: Model Interactions and Their Biophysical Basismentioning
confidence: 99%
“…The original MJ potential (Table V of [329]), as was used in [40,153,296,330], embodies the hydrophobic effect, thus it tends to place non-polar residues in the folded protein core as in real proteins (reviewed in [116,204]). However, certain modified, 'shifted' forms of MJ potentials that are similar to table VI of [329] with prominent repulsive energies [331] do not embody this biophysical property (reviewed in [158,204]), making it problematic to interpret some of the predictions from such models. For instance, in some cases, a shifted-MJ potential may lead to nominally charged residues instead of hydrophobic residues occupying the core of a model protein [114,204,331].…”
Section: Model Interactions and Their Biophysical Basismentioning
confidence: 99%
“…Using lattice simulations as mentioned above, Abkevich et al (1994) observed that a structure with mostly non-local contacts folded two orders of magnitude faster than one with mostly local contacts. Juraszky et al (Juraszek and Bolhuis 2006) found that in the folding of the small protein, i.e., the WW cage, 80 % of the pathways are initiated by NLI while secondary structures appear later.…”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 97%
“…Several other small single domain proteins were later shown to fold in a similar way [3]. The two state mechanism provided the basis for a nucleation-condensation mechanism, with folding through simultaneous formation of secondary and tertiary structure centered around a small folding nucleus [4,5]. Recent work on the homeodomain superfamily [6,7] and on a PDZ domain [8], led to the view that the framework and nucleation-condensation models represent extreme manifestation of an underlying common mechanism and that proteins may appear to fold by either the nucleation-condensation or framework mechanism depending on the inherent stability of their secondary structure elements [7,9].…”
Section: Introductionmentioning
confidence: 98%